Analysis of the Causes of High Maternal Mortality Rates in Hospitals: Contributing Factors and Solutions for Improvement - Ramadhani, Meutia; Rukaiyah, Rukaiyah (International Journal on ObGyn and Health Sciences, 2025)
This research investigates the causes of high maternal mortality rates in hospitals, aiming to identify key contributing factors and propose solutions for reducing preventable deaths. By analyzing hospital records, conducting interviews with healthcare providers, and reviewing patient surveys, the study explores a range of issues, including healthcare infrastructure, staffing levels, medical practices, socio-economic barriers, and cultural factors. The findings highlight the critical role of well-resourced healthcare systems, efficient management practices, and timely interventions in improving maternal outcomes. Additionally, socio-economic and cultural barriers were identified as significant contributors to high mortality rates, particularly among vulnerable populations. The study underscores the importance of improving access to quality maternal care, enhancing healthcare provider training, and addressing systemic inequalities. The research concludes with a call for sustained action, policy reforms, and further research, particularly focusing on long-term interventions and targeted support for at-risk groups, to effectively reduce maternal mortality rates and improve global maternal health.